Blastogenic response of human lymphocytes to oral bacterial antigens: comparison of individuals with periodontal disease to normal and edentulous subjects. - Patters, M R (1976)
Cell-mediated immunity in humans to antigens derived from oral plaque bacteria was investigated by using the lymphocyte blastogenesis assay. Subjects with varying severities of periodontal disease including normal, gingivitis, periodontitis, and edentulous were compared. Mononuclear leukocytes were separated from peripheral blood and cultured with antigens prepared by sonication of Actinomyces viscosus (AV), Actinomyces naeslundii (AN), Veillonella alcalescens (VA), Leptotrichia buccalis (LB), Bacteroides melaninogenicus (BM), and homologous dental plaque (DP). The lymphocyte response of subjects with gingivitis or periodontitis was significantly greater than that of normal subjects to antigens of AV, AN, and DP, but did not differ from the response of edentulous subjects. Periodontitis subjects were significantly more reactive than edentulous and normal subjects in response to VA, LB, and BM. These findings suggest that the tested gram-negative bacteria and the host response they evoke are associated with advanced periodontal destruction.